Evaluation of ICT Integration in Teaching and Learning among Nigerian Tertiary Institution Lecturers using the Technology Acceptance Model (TAM) - Kayode Sunday John, DADA (Information Research Communications, 2025)
This study evaluates the integration of Information and Communication Technology (ICT) in teaching and learning among lecturers in Nigerian tertiary institutions, employing the Technology Acceptance Model (TAM). A structured quantitative survey approach was employed within the sample of 414 lecturers drawn from five public universities. To this study, a validated 5-point Likert scale ICT questionnaire measuring Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), proactive and reactive attitude toward use, behavioral intention, and actual use of ICTs was used. The constructs were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that PU (β=0.42, p<0.001) and PEOU (β=0.35, p<0.001) positively and significantly predicted the attitudes of lecturers which, in turn, positively and significantly Behavioral Intention (β=0.48, p<0.001) and actual use (β=0.52, p<0.001) with 58% of the variance in intention and 47% in use explained. The measurement model provided evidence of reliability (CR>0.80, AVE>0.50) and validity (HTMT<0.85) of the constructs. The demographic characteristics of the sample indicated that the sample was predominantly male (55%) and mid-aged (62% between 35-50 years), mid experienced (68.1% of the sample having 5-15 years) with a background in sciences (30%) as the most common. Challenges, including unreliable internet and limited infrastructure, were noted, consistent with regional studies. The results of the findings affirm TAM’s applicability in modeling ICT adoption in Nigerian higher education, and recommended the need for enhanced training, infrastructure investment, and policy reforms to address barriers and promote sustainable ICT integration, aligning with Nigeria’s educational goals.
Keywords: Higher education; ICT integration; Lecturers; Nigerian tertiary institutions; Teaching and learning; Technology Acceptance Model.